235k views
1 vote
Can someone help me solve this?

Can someone help me solve this?-example-1

2 Answers

5 votes
The first one can be -4+2= -2
User Mynameiscoffey
by
5.1k points
2 votes

Answer:

p + q = (-2) --------(1)

p - q = 8 ----------(2)

on simplifying both equati

8 + q = (-2)-q

q + q = (-2) -8

2q = (-10)

q = (-10)/2

q = (-5)

putting the value of q = (-5) in the equation

p + (-5) = (-2)

p = (-2)+5

p = 3

hence, p = 3 , q = (-5)

User Simply Brian
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.